BRAND LOYALTY AND HALAL AWARENESS FOR HALAL BEVERAGE PRODUCT AMONG GEN Z - Damayanti, Luthfia Rayhan; Puspita, Rosana Eri (ULTIMA Management, 2023)
Abstract- Nowadays, many mineral waters have sprung up with various brands, including Le Minerale. However, some consumers do not know the importance of sorting and choosing mineral water products regarding brand image and halal awareness in increasing brand loyalty through trust in a brand. So, this study aims to determine the influence of brand image and halal awareness on Le Minerale product brand loyalty with brand trust as a mediation variable. The Grand Theory in this study is the Theory of Planned Behavior (TPB). This study used quantitative methods with data collection techniques carried out through the distribution of questionnaires with Likert scale measurements. The sample used was 90 Generation Z Muslim consumers (aged 13-28 years) who had consumed Le Minerale products. Sampling technique using KMO. This study uses multiple analysis tests supported by validity and reliability tests statistical tests, namely the T-test, F-test, R2 test, classical assumption test, and Sobel test. The study results showed that the variables of brand image, halal awareness, and brand trust positively and significantly affected brand loyalty. Then, brand image and halal awareness positively and significantly affected brand trust. Furthermore, the Sobel test brand trust test can mediate brand image and halal awareness of brand loyalty. Keywords: Brand Image; Brand Loyalty; Brand Trust; Halal Awareness; Mineral Water